Could mean platelet volume among complete blood count parameters be a surrogate marker of metabolic syndrome in pre-pubertal children?. (September 2014) - Aypak, Cenk; Türedi, Özlem; Bircan, Mustafa A.; Yüce, Adnan
Abstract Interest in childhood metabolic syndrome (MetS) has increased substantially due to the increasing prevalence of childhood obesity on a global scale. Early recognition of MetS is critical in order to delay the development of cardiovascular disease (CVD). In this study, we evaluated the relationship between complete blood count (CBC) parameters and MetS among pre-pubertal children which may provide evidence in support of using low cost, readily available clinical haematological parameters for the detection of MetS. A retrospective analysis was carried out on 330 (125 lean vs. 205 overweight) Turkish pre-pubertal children who attend to a paediatric outpatient clinic. Age, gender, puberty, body mass index, CBC parameters, cardiometabolic risk factors including lipid profiles, high sensitive serum reactive protein (hsCRP) and insulin resistance index calculated by homeostasis model assessment (HOMA-IR) were evaluated and compared among lean, overweight children and children with MetS. The mean age of the study population was 7.4 ± 1.9 years. In both gender, the mean values of mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH) and mean corpuscular haemoglobin concentration (MCHC) were significantly lower and red blood cell (RBC), platelet (PLT) counts were significantly higher in overweight children. Overall, 8.4% (n = 28) of patients met the criteria of MetS. Children with MetS had higher levels of PLT and lower levels of mean platelet volume (MPV). Of all the haematological parameters analysed, PLT was positively, whereas MPV was negatively correlated with MetS in girls. In addition, MPV was inversely correlated with fasting blood glucose, HOMA-IR, low density lipoprotein-cholesterol (LDL-C) and low density lipoprotein-cholesterol/high density lipoprotein-cholesterol (LDL-C/HDL-C) ratio in girls after adjusting for confounding factors. The risk analyses of MetS in terms of MPV quartiles showed that the adjusted OR (95% CI) for the lowest vs. the highest quartile was 7.71 (1.45–40.89) in girls. These data might suggest that MPV could be another feature of MetS in pre-pubertal girls and might be used as a surrogate marker for MetS in clinical settings.